Frailty in COPD: Clinical Impact, Diagnosis, Biomarkers, and Management Strategies - Azhimamatova R; Salieva RS; Zalova TB; Karimova K; Karimova DS; Dyikanova SA; Kalmatov R; Tynaliev UM (International Journal of COPD)
Rakhima Azhimamatova,1 Rana Sherbaevna Salieva,1 Tazagul Bayishbecovna Zalova,1 Kunduzkhan Karimova,2 Dilshat S Karimova,2 Shekerbubu Anarbekovna Dyikanova,2 Roman Kalmatov,1 Urmatbek M Tynaliev3 1International Medical Faculty, Osh State University, Osh City, Kyrgyz Republic; 2Institute of Economy, Business and Management, Osh State University, Osh City, Kyrgyz Republic; 3Directorate for Research and Doctoral Education, Jusup Balasagyn Kyrgyz National University, Bishkek City, Kyrgyz RepublicCorrespondence: Urmatbek M Tynaliev, Email urmat.tynaliev@knu.kgAbstract: Frailty is a complex clinical syndrome characterized by reduced physiological resilience and heightened susceptibility to external stressors, culminating in increased risks of functional decline, hospitalization, and mortality. In individuals with chronic obstructive pulmonary disease (COPD), frailty exacerbates disease burden and is closely linked to adverse outcomes, including increased exacerbation frequency, diminished quality of life, and poor prognosis. This review synthesizes current evidence on the interplay between frailty and COPD, emphasizing clinical implications, diagnostic frameworks, emerging biomarkers, and tailored management strategies. A systematic literature search was conducted across PubMed, Scopus, and Embase databases, employing key terms such as “frailty”, “chronic obstructive pulmonary disease”, “COPD”, “frailty assessment”, “biomarkers”, and “frailty management in COPD”. Inclusion criteria targeted English-language studies reporting original data with a direct focus on frailty in the context of COPD. By synthesizing multidimensional assessment strategies and potential therapeutic modalities, this review supports the development of precision-based interventions to reduce frailty and improve outcomes in patients with COPD.Keywords: frailty, COPD, frailty assessment, frailty scales, frailty biomarkers